PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 004 KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU - Rika Rika; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research is based on the averaga much lawer student learn science bg the number of student who did not complete that 22 student 73 %. The purpose of this research is to improve learning outcomes by implementing the model study contextual teaching and learning can improve that result learn the class student Ivso elementary school country 004 Sungai Lala? This research method use the research of class action. This research is with two cycle with every cycle twice meeting and once daily restaling. This research entangle the class student IV elementary school country 004 Sungai Lala as much 30 student people.This action is from Maret until April 2015. Result learn the IPA obtained from data of early horizontaly flatten 59,47 categorize less completely minimize bs with the standard KKM. At cycle of I UH I obtained to flatten to flatten the result learen the IPA 64,77 kategorize enaugh,hereinafter at cycle of II UH II of result of learning to mount to return to become 73,83 categorize good ness. Result of research first cycle teacher less comprehend model Contextual teaching and learning is difficult to so.that apply bat at second cycle.Use of method of contextual teaching and learning have applicable maximally.This marking with many complete student in lesson IPA conclusion from this research applying model the contextual teaching and learning have succeeded aplied in an optimal fashion in result learn the IPA of IV SDN 004 Sungai Lala.Key word : contextual teaching and learning, result learn the IPA